Inconsistencies about key terms in teaching strategic management - Marić Dragić (Naučne publikacije Državnog univerziteta u Novom Pazaru, 2020)
The article investigates inconsistencies about key concepts and other issues of strategic management theory in the relevant literature at domestic universities, with the aim of pointing out the resulting difficulties in teaching relevant subjects. Numerous inconsistencies in textbook and similar management texts have been established, which are not only a consequence of the underdevelopment of the stated theory, as well as the allowed authorial freedom. Primarily, differences in the understanding of key concepts of strategic management were highlighted, especially the concept of management - including its understanding as a science or skill, as well as different representations of its principles. Then, the difficulties and differences in defining the concept of strategy, strategic management and policy itself, as well as the relationship between the concepts of vision and mission were highlighted. Some of the researched differences in the presentation of key concepts and issues of strategic management were assessed as justified, and some of the unjustified ones were given a proposal for appropriate harmonization in order to relieve the users of the relevant literature.